CONSTRUCTIVIST APPROACHES IN ENGLISH LANGUAGE LEARNING: THEORY INTO PRACTICE (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
Constructivist approaches in English Language Learning (ELL) emphasize the active role of learners in constructing knowledge through real-life experiences, social interaction, and critical reflection. This paper explores the theoretical foundations of constructivism and its practical implementation in ELL classrooms. Based on qualitative classroom research, the study outlines the benefits of constructivist pedagogy for learner autonomy, communication, and engagement, while also addressing its limitations such as uneven participation, time constraints, and assessment complexity.